2013
DOI: 10.1016/j.chc.2012.12.001
|View full text |Cite
|
Sign up to set email alerts
|

The State of the Evidence Base for Psychodynamic Psychotherapy for Children and Adolescents

Abstract: This paper reviews the outcomes of psychodynamic psychotherapy (PP) for children and adolescents reported in papers identified by a comprehensive review of the literature on treatment evaluations of psychological and medical interventions for mental disorders in pediatric populations. The review identified 48 reports based on 33 studies. Reports were individually evaluated in terms of methodological rigor.Randomized trials, quasi-experimental and observational studies are considered separately. RCTs were indep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
32
0
9

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 99 publications
2
32
0
9
Order By: Relevance
“…Just as a mother tries to understand and respond to her infant's emotions and needs, so too must the therapist try to address the patient's demands and troubles. In this sense, Palmer et al (2013) state that much of what they had noted as "nontraditional applications of psychoanalytic therapy may actually end up as the most commonly used methods for delivering these therapeutic ideas. And why not?"…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Just as a mother tries to understand and respond to her infant's emotions and needs, so too must the therapist try to address the patient's demands and troubles. In this sense, Palmer et al (2013) state that much of what they had noted as "nontraditional applications of psychoanalytic therapy may actually end up as the most commonly used methods for delivering these therapeutic ideas. And why not?"…”
Section: Discussionmentioning
confidence: 99%
“…It is important to note that the symptoms that led Alice to be referred for therapy included somatization, and that she was still mourning the loss of her father. When working with children, therapeutic characteristics such as affective involvement, an impartial approach, and attunement of language and affect may be needed to a greater extent than when treating adults (Goodman, 2015;Palmer, Nascimento, & Fonagy, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, research examining the efficacy and effectiveness of child psychodynamic psychotherapy lagged behind, although some recent publications have been showing a growing interest in this field (Deakin & Nunes, 2008;Goodman & Athey-Lloyd, 2011;Kennedy & Midgley, 2007;Midgley & Kennedy, 2011;Midgley, Anderson, Grainger, Vuckovic-Nesic, & Urwin, 2009;Palmer, Nascimento & Fonagy, 2013). In addition, although there is an increase of studies on child psychodynamic psychotherapy, indicating an evidence base on the effectiveness and efficacy of this psychotherapeutic modality, the need for more research in this field remains, especially considering that the therapeutic process is still poorly understood.…”
mentioning
confidence: 99%
“…Based on these assumptions, psychodynamic therapists continue to apply this approach in the treatment of the disorder, reporting good results (Bromfield, 2000;Fonseca, 2009;Goodman & Athey-Lloyd, 2011;Olesker, 1999;Pozzi, 2003;Shuttleworth, 1999;Topel & Lachmann, 2008). Shuttleworth (1999) has suggested that children with Asperger's disorder share some similarities with adults with narcissistic personality disorder and can be subjected to psychoanalytic intervention.…”
mentioning
confidence: 99%
“…In fact, considering the high rate of incidence of psychopathology in developmental age and according to the literature and international guidelines in infant mental health, it is becoming increasingly important to explore the theme of evaluation of treatment in order to understand what the most effective method of intervention (De Coro et al, 2010;Palmer, Nascimento & Fonagy, 2013;Leichsenring, Leweke, Klein & Steinert, 2015). In the last ten years we have seen a rapid increase of studies that deal with the effectiveness of the assessment in the context of interventions run during adulthood (Dazzi, 2006;Midgley & Kennedy, 2011;Lenzo, Gargano, Mucciardi, Lo Verso & Quattropani, 2014) while there are few similar studies focusing on developmental age (Palmer et al, 2013).…”
Section: Introductionmentioning
confidence: 99%